KEPUASAN REMAJA TERHADAP PELAYANAN SOSIAL DI PANTI PEMBERDAYAAN SOSIAL BINA REMAJA (PPSBR) LEMBANG KABUPATEN BANDUNG BARAT - Galih Suseno; Bambang Rustanto; Diana Diana (Indonesian Journal of Social Work, 2024)
Satisfaction about social service is a pleased or disappointed feelings which appear after comparing between perception or impression with the provided services by social service institution. The objectives of this research are able to achieve empirical descriptions about: 1. Respondent’s characteristics, 2. Basic needs fulfillment service for respondents, 3. Social service’s quality and facility for respondents, 4. Respondent’s relationship with the institution’s officers. The design of this research is a quantitative survey descriptive research. The populations in this research are 50 adolescents who are being benefit recipients in PPSBR Lembang Kabupaten Bandung Barat. The sampling thechnic of this research is using census thechnic of all the populations to be going to use as the research sample. The data collection thecnic is using questionnaire and the measurements tools are using Rating Scale. The results of this research show that the levels of adolescent’s satisfaction about social service at PPSBR Lembang Kabupaten Bandung Barat is in high level category. Basic needs fulfillment service for respondents is in medium level category. Social service’s quality and facility for respondents is in high level category. And Respondent’s relationship with the institution’s officers is ini high level category. Based on the problem’s analysis in this study it is suggested an altenative program is “Social extension about Social Service Enhancement Quality for Institution’s Officers at Panti Pemberdayaan Sosial Bina Remaja (PPSBR) Lembang Kabupaten Bandung Barat”.